GRID-CONNECTED PHOTOVOLTAIC SYSTEM DESIGN FOR LOCAL GOVERNMENT OFFICES IN NIGERIA (Nigerian Journal of Technology, 2017)
Photovoltaic is direct conversion of sunlight into electricity through electronic means that occurs at atomic level of semiconductors materials. It is neat, silent and elegant process of generating electric power in environmentally friendly manner. In this paper, the design analyses roof-mounted Grid-connected 148.5kWp Photovoltaic System with Energy Storage for use in a Local Government secretariat in Nigeria. The design was simulated using PV*SOL software to evaluate the system’s production performance and to know the amount of electric power generation for every day of the year. The result shows that the PV system’s daily production far exceeds energy demand in the building. The maximum monthly demand is 2893.22kWh while the least energy production is 13,802kWh which occur in July. The highest production occurs in November with 20,258kWh; followed by March energy yield of 20,053kWh. Hence, the system could serve as good revenue source for the government by exporting more than 75% of the power generated to the grid in exchange for good cash from electricity utility; while at same time serving as motivation for home owners in the community as well as other governmental offices to generate some or all of their energy need.http://dx.doi.org/10.4314/njt.v36i2.33